Diabetogenic effect of hepatitis C virus and insulin resistance among chronic hepatitis C patients - Mohamed Sayed Hassan; Yousra Hamed Mourad; Mohammad Ahmad Elghobary (SpringerOpen, 2016)
Context Hepatitis C virus (HCV) is a major cause of chronic liver disease worldwide. In addition to established liver injury, type 2 diabetes mellitus is one of the most important extrahepatic metabolic disorders that are attributed to HCV infection. Aim The aim of this study was to investigate the impact of HCV infection in insulin resistance (IR). Patients and methods Our study included 100 patients with HCV who were divided into two groups according to the presence and absence of diabetes and 25 diabetic patients who served as a control group. They were subjected to full medical history and examination and laboratory investigations including high-sensitivity C-reactive protein (CRP), serum tumor necrosis factor α (TNF-α), interleukin 6 (IL-6), fasting insulin, and fasting glucose. Results Our study showed increased IR among diabetic HCV-infected patients (group I) with a mean level of homeostasis model assessment of IR of 3.02, 1.457, and 1.064 in groups I, II, and III, respectively. There was also an increased level of proinflammatory cytokines (CRP, TNF-α, and IL-6) in this group, with mean levels of high-sensitivity CRP of 9.448, 7.7062, and 5.8229 mg/dl in groups I, II, and III, respectively. The mean level of IL-6 in group I was 215.63 pg/ml, in group II it was 167.62 pg/ml, and in group III it was 173.72 pg/ml. The mean level of TNF-α was 626.12, 618, and 422.76 pg/ml in groups I, II, and III, respectively, suggesting the role of proinflammatory cytokines in the pathogenesis of IR in chronic HCV. Conclusion HCV infection is associated with an increased level of proinflammatory cytokines that play a crucial role in the pathogenesis of IR in chronic HCV.